Helicobacter pylori induces intracellular galectin-8 aggregation around damaged lysosomes within gastric epithelial cells in a host O-glycan-dependent manner. (5th October 2018) - Li, Fang-Yen; Weng, I-Chun; Lin, Chun-Hung; Kao, Mou-Chieh; Wu, Ming-Shiang; Chen, Huan-Yuan; Liu, Fu-Tong
Abstract: Galectin-8, a beta-galactoside-binding lectin, is upregulated in the gastric tissues of rhesus macaques infected with Helicobacter pylori . In this study, we found that H. pylori infection triggers intracellular galectin-8 aggregation in human-derived AGS gastric epithelial cells, and that these aggregates colocalize with lysosomes. Notably, this aggregation is markedly reduced following the attenuation of host O-glycan processing. This indicates that H. pylori infection induces lysosomal damage, which in turn results in the accumulation of cytosolic galectin-8 around damaged lysosomes through the recognition of exposed vacuolar host O-glycans. H. pylori -induced galectin-8 aggregates also colocalize with autophagosomes, and galectin-8 ablation reduces the activation of autophagy by H. pylori . This suggests that galectin-8 aggregates may enhance autophagy activity in infected cells. We also observed that both autophagy and NDP52, an autophagy adapter, contribute to the augmentation of galectin-8 aggregation by H. pylori . Additionally, vacuolating cytotoxin A, a secreted H. pylori cytotoxin, may contribute to the increased galectin-8 aggregation and elevated autophagy response in infected cells. Collectively, these results suggest that H. pylori promotes intracellular galectin-8 aggregation, and that galectin-8 aggregation and autophagy may reciprocally regulate each other during infection.